Effect of HPHT annealing on the photoluminescence of synthetic diamonds grown in the Fe-Ni-C system - Yelisseyev, A; Lawson, S; Sildos, I; Osvet, A; Nadolinny, V; Feigelson, B; Baker, M; Newton, M; Yuryeva, O (2003)
The photoluminescence (PL) spectra of synthetic diamonds (SD) containing high concentrations of nitrogen and nickel impurities have been examined in both as-grown samples and the ones annealed at 1950 or 2200 K. A large number of zero-phonon lines (ZPLs), including two tens of vibronic PL systems, have been identified and their behaviour on annealing has been studied, one-third of documented lines have also been observed in natural diamonds. An analysis of their behaviour on annealing allows their division into three main groups, namely: (I) The systems present in as-grown SD, but which disappear after annealing at 1950 K; (II) The systems, which appear after annealing at approximately 1950 K, but their intensity is lower or they disappear completely after annealing at 2200 K; (III) The system, whose intensity increases after annealing at 1950 K and does not decrease after further annealing at 2200 K. A combined optical and ESR study allowed one to identify the systems of group I with individual impurities, whereas the items within group III were associated with nickel-nitrogen complexes containing a single nickel ion in the divacancy position surrounded by a few (n≥2) nitrogen atoms. The systems within group II are related to a relaxed single nickel defect (nickel ion in divacancy position) and simple nickel-nitrogen complexes, containing a single nitrogen atom. The PL excitation spectra were measured for 15 most intense PL systems. A broad absorption band in the annealed SD, with a peak approximately 450 nm and a superimposed fine structure, was decomposed into individual components, related to the NE1, NE2 and NE3 paramagnetic centres. The lower excited states of these three centres are split with Δ E=125 meV, 62 meV and 221 meV, respectively, while the spin-allowed electronic transitions take place only to the upper sublevel. © 2003 Elsevier Science B.V. All rights reserved.